#Cleftlip/Palate: What Is the World Talking About?. (September 2020) - Hudson, Alexandra S.; Morzycki, Alexander D.; Guilfoyle, Regan
Objective: Studies have begun analyzing how the world converses on social media platforms about medical/surgical topics. This study's objective was to examine how cleft lip and palate, two of the most common birth defects in the world, are discussed on the social media platform Twitter. No study to date has analyzed this topic. Methods: Tweets were identified using any of the following: cleft, cleft lip, cleft palate, #cleft, #cleftlip, #cleftpalate. Eight months between 2017 and 2018 were analyzed. Main Outcome Measures: The primary outcome was the tweet subject matter. Secondary outcomes were author characteristics, tweet engagement, multimedia, and tweet accuracy Results: A total of 1222 tweets were included. #Cleft was the most common hashtag (71%), and it was significantly associated with more retweets ( P = .03). Twenty-seven countries tweeted, with the United States (34%) and India (27%) producing the most. Charities (36%), hospitals (14%), and physicians (13%) were the most common authors. Over three-quarters of tweets were self-promotional. The top content included charity information (22%) and patients' cleft stories (14%). Tweets about patient safety/care and surgical service trips generated the most engagement. The accuracy of educational tweets was 38% low accuracy and 1% inaccurate. One hundred forty-nine tweets (12%) discussed a published research article, but 41 tweets did not share a link. Conclusions: Charities dominate the cleft lip/palate "Twitterverse." Most tweets were self-promotional, and over a third of educational tweets were low accuracy. As the cleft social media community continues to grow, we recommend using the hashtag #cleft to reach a wider audience.